Management of type IV placenta previa by bilateral internaliliac artery balloon placement - Dandu Ravi Varma; Abhijit S Nair; Gemaraju Vindhya; Saraschandrika (Wolters Kluwer Medknow Publications, 2015)
Mortality and morbidity in parturients with abnormal placentation like grade III and IV of placenta previa, placenta accreta, placenta increta and placenta percreta is very high. Ultrasonography can detect these conditions well in advance and proper planning for delivery can be made. Prophylactic placement of bilateral internal iliac artery balloon has been shown to reduce the blood loss during cesarean section, provide optimal surgical conditions, prevent cesarean hysterectomy on several occasions and in situations where hysterectomy is essential; this procedure has reduced the requirement of massive blood transfusion in the perioperative period. We report successful perioperative management of a parturient who had grade 4 placenta previa in whom prophylactic bilateral internal iliac artery balloon was placed under local anesthesia and the balloon was inflated after the delivery of the baby by lower segment cesarean section (LSCS). After the closure of uterus, the balloon was deflated. No perioperative blood transfusion was required.